Analysis of chronic diseases in Ghana using logistic regression - Karim, Azumah (2014)
A thesis submitted to the Department of Mathematics, Kwame Nkrumah University of Science and Technology in partial fufillment of the requirement for the degree of M.Phil Mathematical Statistics.